Multi‐channel in situ dynamic light scattering instrumentation enhancing biological small‐angle X‐ray scattering experiments at the PETRA III beamline P12. (13th February 2018) - Falke, Sven; Dierks, Karsten; Blanchet, Clement; Graewert, Melissa; Cipriani, Florent; Meijers, Rob; Svergun, Dmitri; Betzel, Christian
Abstract : A novel in situ dynamic light scattering (DLS) module implemented at the PETRA III EMBL beamline P12 is capable of performing real‐time sample solution scoring in parallel with BioSAXS experiments, including a multi‐channel DLS detection principle. Abstract : Small‐angle X‐ray scattering (SAXS) analysis of biomolecules is increasingly common with a constantly high demand for comprehensive and efficient sample quality control prior to SAXS experiments. As monodisperse sample suspensions are desirable for SAXS experiments, latest dynamic light scattering (DLS) techniques are most suited to obtain non‐invasive and rapid information about the particle size distribution of molecules in solution. A multi‐receiver four‐channel DLS system was designed and adapted at the BioSAXS endstation of the EMBL beamline P12 at PETRA III (DESY, Hamburg, Germany). The system allows the collection of DLS data within round‐shaped sample capillaries used at beamline P12. Data obtained provide information about the hydrodynamic radius of biological particles in solution and dispersity of the solution. DLS data can be collected directly prior to and during an X‐ray exposure. To match the short X‐ray exposure times of around 1 s for 20 exposures at P12, the DLS data collection periods that have been used up to now of 20 s or commonly more were substantially reduced, using a novel multi‐channel approach collecting DLS data sets in the SAXS sample capillary at four different neighbouring sample volume positions in parallel. The setup allows online scoring of sample solutions applied for SAXS experiments, supports SAXS data evaluation and for example indicates local inhomogeneities in a sample solution in a time‐efficient manner. Biological macromolecules with different molecular weights were applied to test the system and obtain information about the performance. All measured hydrodynamic radii are in good agreement with DLS results obtained by employing a standard cuvette instrument. Moreover, applying the new multi‐channel DLS setup, a reliable radius determination of sample solutions in flow, at flow rates normally used for size‐exclusion chromatography–SAXS experiments, and at higher flow rates, was verified as well. This study also shows and confirms that the newly designed sample compartment with attached DLS instrumentation does not disturb SAXS measurements.